Presepsi Keadilan, Sistem Perpajakan, Diskriminasi, dan Tax Knowledge Terhadap Kepatuhan Wajib Pajak Mengenai Perilaku Etika Penggelapan Pajak (Tax Evasion) - Cahyani, Rizkha Gita; Triyono (ITB AAS Indonesia Surakarta, 2025)
This study aims to analyze the influence of perceptions of fairness, taxation systems, discrimination, and tax knowledge on taxpayer compliance related to ethical tax evasion behavior. The background of this study is based on the still low level of tax compliance in Indonesia and the high potential for tax evasion that can harm the state. This study uses a quantitative approach with a data collection method through a questionnaire distributed to 196 individual taxpayer respondents registered at KP2KP Purwodadi. The data analysis technique uses the Structural Equation Modeling - Partial Least Square (SEM-PLS) model through SmartPLS 3.0 software. The results of the study indicate that perceptions of fairness, taxation systems, and tax knowledge have a significant effect on taxpayer compliance in the context of tax evasion ethics. However, the discrimination variable does not show a significant effect. These findings indicate that increasing fairness and understanding of taxation, as well as a transparent and efficient taxation system, can increase taxpayer compliance and reduce the potential for tax evasion. This study contributes to efforts to develop a fairer and more strategic tax system in increasing public tax compliance.